What’s Wrong with Lyotard Paradigm? The Repudiation of Generalization and The Diversity of Research Area in Accounting - Suham Cahyono; Tjiptohadi Sawarjuwono (Global Financial Accounting Journal, 2022)
Purposes - This study aims to investigate the Lyotard paradigm that dominates the framework of research in accounting and finance, especially the concept of generalizing the results of studies that apply a quantitative approach. Research Method - This study is a literature study that uses secondary data from various articles, journals, library books and also Scopus journal articles to provide a lot of evidence related discussion topic. We obtained data for nearly 40 articles from a database of reputable national and international journals indexed by Scopus and Google scholar. Findings - The results of this study show that many scholars alignment with lyotard perspective has been refuted by several axioms and new paradigms that have developed in the midst of the turmoil of research in accounting and finance, so that this has led to various rejections and expansion of studies in accounting and finance, especially studies that use a critical research approach. and postmodernism Implications - The main contribution of this study is to provide a wider literature on research perspectives in accounting and finance, especially for researchers who want an approach that applies an expanded study result. The limitation of this research is that it only considers Lyotard's approach to the generalization paradigm in addition to other approaches such as Derrida and Machiavellianism.